Reka bentuk dan pembangunan pembelajaran atas talian menggunakan sumber terbuka dalam pengurusan dan kepimpinan pendidikan - Norazah Nordin; Sham Ibrahim; Zamri Mahamod; Mohd. Izham Mohd. Hamzah (Penerbit Universiti Kebangsaan Malaysia, 2009)
This study aimed to investigate the use of e-learning among school heads in educational management and educational leadership. The study was conducted in two phases. The Þrst was to develop an e-learning management system using open source software, Moodle. This phase emphasized on the processes involved in designing and developing the e-learning management system prototype, named e-Headship. The content of e-Headship was related to modules on the National Professional QualiÞcation for Headship(NPQH) programme. The second phase of the study was the evaluation of e-Headship. The elements evaluated in this paper were the e-learning content. The participants involved were those trained as future heads of schools in Malaysia. They were all trained at Institut Aminudin Baki (IAB), an institute for training schools’ administrators. Using quasi-experimental study design, the study analyzed participants’ respond towards the usage of e-Headship. The sample of the study comprised of 60 school heads from one cohort. Analysis of data was done based on the parametric approach. The researchers had designed and developed various instruments (which were represented in the form of surveys) for measuring 47 effectiveness of e-Headship based on the participants’ knowledge, usage, skills and cognitive level. Generally, the fi ndings of the research showed that the use of e-Headship based in the participants’ knowledge, usage, skills and cognitive level was signifi cantly more effective as compared to the use of conventional teaching and learning method. It was hoped that the use of such prototype would help IAB in designing and developing better programmes that could benefi t the participants at large